Challenges in measuring complications and death due to invasive Salmonella infections. (19th June 2015) - Qamar, Farah Naz; Azmatullah, Asma; Bhutta, Zulfiqar A.
Abstract: Despite the highest burden of Typhoid fever in children globally, exact estimates of morbidity and mortality are lacking due to scarcity of published data. Despite a high prevalence and a socioeconomic burden in developing countries, published data with morbidity and mortality figures are limited especially Africa and South American regions. Data from the community is insufficient and most case fatality estimates are extrapolations from hospital based studies that do not cover all geographical regions, and include cases which may or not be culture confirmed, MDR resistant or sensitive cases, or from mixed populations of age (adults and children). Complications of typhoid such as intestinal perforation, bone marrow suppression, and encephalopathy are dependent on MDR/Fluoroquinolone resistant Salmonella infection, comorbidities such as malnutrition, and health-care access. Data is again insufficient to estimate the true burden of Typhoid Fever in different regions and groups of populations. Although there has been a rapid decline in cases in developed countries with the advent of improved sanitization, timely and easy access to health care and laboratories, this is still not the case in the developing countries where Typhoid deaths are still occurring. The way forward is to develop rapid and cost effective point of care diagnostic tests, put in place validated clinical algorithms for suspected clinical cases, and design prospective, and community based studies in different groups, implement maintenance of electronic health records in large public sector hospitals and regions to identify populations that will benefit most from the implementation of vaccine. Policies on public health education and typhoid vaccine may help to reduce morbidity and mortality due to the disease.